PEMENUHAN HAK KORBAN DALAM PENERAPAN PENGEMBALIAN ASET PADA KASUS PENIPUAN E-DINAR COIN CASH - Windu Farjana (2023)
Technology through media networks is very developed, so that in their daily lives people cannot be separated from the internet, including the economy. Technological developments in terms of investment can be done without the need to come to an investment company, but only download the application and register online. In addition to the ease of registering, people are also offered a variety of investment products and can invest according to their wishes. This can be a problem if people are not careful in choosing the product they want to invest in and the worst possibility is to become a victim of illegal or fraudulent investment. Illegal investments can be found in ponzi schemes to attract victims. The problem formulations in this research are: (1) How is the return of assets of victims of fraud according to positive law in Indonesia? (2) How is the fulfillment of victims' rights in returning E-Dinar Coin Cash fraud assets? This research is normative legal research, with a statute approach and case approach. The research shows that the victim's loss cannot be returned to the victim. The results showed that the positive law regarding asset recovery in Indonesia has not been able to reach the assets resulting from criminal acts. The role of the government through the Financial Services Authority and professional law enforcers is needed to overcome cases of fraud, one of which is illegal investment so that victims' losses can be returned.